Social protection and response to COVID-19 in Latin America and the Caribbean: Innovations in registration and payment systems - Nurth Palomo; Luis Vargas Faulbaum; Anna Carolina Machado; Camila Rolon; Fabio Veras Soares; Mónica Rubio; Florencia Alejandre; Gerardo Escaroz (International Policy Centre for Inclusive Growth (IPC-IG), 2022)
The outbreak of the COVID-19 pandemic has hit the foundations of the economy and provoked devastating social effects in all the countries in the world, being Latin America and the Caribbean (LAC) one of the most affected regions. This report updates the regional overview of the response measures to the pandemic, details cash transfer programmes and analyses their coverage and discusses the challenges in adopting these innovations during the response to the first outbreak of the virus in Latin America and the Caribbean.
Keywords: 330; COVID-19; pandemic response; social protection; Latin America and the Caribbean; Coronavirus; Soziale Sicherheit; Öffentliche Sozialleistungen; Lateinamerika; Karibischer Raum